PERANCANGAN WEBSITE KEMITRAAN DALAM MENUNJANG PROGRAM KEMITRAAN DAN BINA LINGKUNGAN PT ANGKASA PURA I - Al Adawiah, Fitrah Rabiah; Chairunisa, Frida (Politeknik STIA LAN Makassar, 2023)
PT Angkasa Pura I is a state-owned enterprise (BUMN) that operates in the airport industry. The Partnership and Community Development Program is one of the necessary programs that must be implemented by every BUMN. The PT Angkasa Pura I Sultan Hasanuddin branch's approach to administering this Partnership Program remains traditional. Based on these issues, the objective of the study was to make it easier for prospective foster partners and the general public to obtain information about this program, as well as to simplify the registration procedure for prospective foster couples. This study applied qualitative approaches. As data analysis approach, researchers employed data reduction, data display, and making conclusions. Primary data and secondary data are the two types of data sources used in this study, and membercheck is used to validate the data. The study's findings include a website design that may be used as an information medium as well as a medium for registering possible foster partners. Researchers use five information system components during the website creation process: hardware, software, data, procedures, and people. The website design will make it easier for foster partners and CSR officers to undertake partnership and environmental development projects. This website design includes registration features, catalogues, program information, announcements, and information about this collaboration initiative.